Design and synthesis of hybrid compounds as novel drugs and medicines. Issue 30 (6th July 2022) - Alkhzem, Abdulaziz H.; Woodman, Timothy J.; Blagbrough, Ian S.
Abstract : Hybrid compounds (L1–L2) possess potential advantages over mixtures used in combination therapies. Abstract : The development of highly effective conjugate chemistry approaches is a way to improve the quality of drugs and of medicines. The aim of this paper is to highlight and review such hybrid compounds and the strategies underpinning their design. A variety of unique hybrid compounds provide an excellent toolkit for novel biological activity, e.g. anticancer and non-viral gene therapy (NVGT), and as templates for killing bacteria and preventing antibiotic drug resistance. First we discuss the anticancer potential of hybrid compounds, containing daunorubicin, benzyl- or tetrahydroisoquinoline-coumarin, and cytotoxic NSAID-pyrrolizidine/indolizine hybrids, then NVGT cationic lipid-based delivery agents, where steroids or long chain fatty acids as the lipid moiety are bound to polyamines as the cationic moiety. These polyamines can be linear as in spermidine or spermine, or on a polycyclic sugar template, aminoglycosides kanamycin and neomycin B, the latter substituted with six amino groups. They are highly efficient for the delivery of both fluorescent DNA and siRNA. Molecular precedents can be found for the design of hybrid compounds in the natural world, e.g., squalamine, the first representative of a previously unknown class of natural antibiotics of animal origin. These polyamine-bile acid ( e.g. cholic acid type) conjugates display many exciting biological activities with the bile acids acting as a lipidic region and spermidine as the polycationic region. Analogues of squalamine can act as vectors in NVGT. Their natural role is as antibiotics. Novel antibacterial materials are urgently needed as recalcitrant bacterial infection is a worldwide problem for human health. Ribosome inhibitors founded upon dimers of tobramycin or neomycin, bound as ethers by a 1, 6-hexyl linker or a more complex diether-disulfide linker, improved upon the antibiotic activity of aminoglycoside monomers by 20- to 1200-fold. Other hybrids, linked by click chemistry, conjugated ciprofloxacin to neomycin, trimethoprim, or tedizolid, which is now in clinical trials.